Experimental Study on Heat Recovery System of Exhaust Gases in an Internal Combustion Engine Using Thermoelectric Generators - Nur Athirah Suhaimi; Baljit Singh; Muhammad Fairuz Remeli (Engineering Research: Perspectives on Recent Advances Vol. 2, 2025)
Internal combustion engines do not effectively convert energy from the fuel reaction into useful energy, notably mechanical energy. Vehicle emissions have become a main concern in the recent past. As the population grows, the number of vehicles also increases to meet the mobility demand. In 2012, worldwide production of vehicles reached 84.1 million units, as reported by the Organisation of Motor Vehicle Manufacturers (OICA). In fact, the majority of the energy is converted into heat energy and dissipated into the environment which does not fully contribute to the performance of internal combustion engine. This results in lower overall efficiency of the engine. The heat released into the environment can be converted into useful electrical energy by using a thermoelectric generator (TEG). TEG consists of a cold side and a hot side and works based on the principle of the Seebeck effect. The hot side of TEG is exposed to the hot surfaces of the exhaust, and the cold side is cooled with fan cooled heat sink. The function of a heat sink is to increase the temperature differences across the TEG. The conversion of waste heat into electricity by TEG in an automobile can be a good case study to replace the alternator for battery charging and increase the overall efficiency of the Internal Combustion (IC) engine. This is an experimental study on the waste heat recovery system of an internal combustion engine using thermoelectric technology. In this study, eight pieces of TEG with dimensions of 40 mm x 40 mm each were attached to a square heat exchanger. This heat exchanger was connected to the exhaust pipe of the engine. The temperature recorded in the exhaust was around 100 0C. Thermocouples were embedded on the hot side and cold side of the thermoelectric generators to evaluate the temperature differences across the TEGs. The output of the TEGs was obtained at idle and half-throttled engine conditions. An electronic load was applied to obtain the voltage, current and power output from the TEGs system. The TEGs were tested individually, all connected in series and parallel connections. The maximum output voltage was recorded for the series connections at 5.8 V with an average temperature gradient of 20 0C across TEGs. Maximum power output obtained when all the TEGs connected in series was at 2.3 W. The study concluded that as the number of vehicles increases every year, exhaust waste heat is considered as the future hybrid technology available on vehicles.